The influence of acoustic nonlinearity on absorption properties of Helmholtz resonators. Part II. Experiment - M. MEISSNER (Archives of Acoustics, 2000)
An experimental study of an effect of the acoustic nonlinearity on absorption properties of Helmholtz resonators is presented in this work. By use of the classical standing wave method the changes in the absorption coefficient and the resonators impedance were investigated at moderate and high amplitudes of incident wave. As a result of nonlinearity a high absorption at resonance frequencies was observed and then a decrease in this absorption with increasing amplitude. Measurements of the total loss resistance of resonators have indicated that a change in the resistance at high amplitudes depends strongly on resonator orifice area, the smaller area - the higher increase in the resistance. The experimental results have also shown a growth in resonators reactance which causes an increase in resonance frequency. Quite a good agreement between experimental data and the theory presented in Part I was found.